Stable H–C–O isotope and trace element geochemistry of the Cummins Range Carbonatite Complex, Kimberley region, Western Australia: implications for hydrothermal REE mineralization, carbonatite evolution and mantle source regions - Downes, P.; Demeny, A.; Czuppon, G.; Jacques, A.; Verrall, M.; Sweetapple, M.; Adams, D.; McNaughton, Neal; Gwalani, L.; Griffin, B.J. (Springer, 2014)
The Neoproterozoic Cummins Range Carbonatite Complex (CRCC) is situated in the southern Halls Creek Orogen adjacent to the Kimberley Craton in northern Western Australia. The CRCC is a composite, subvertical to vertical stock ∼2 km across with a rim of phlogopite–diopside clinopyroxenite surrounding a plug of calcite carbonatite and dolomite carbonatite dykes and veins that contain variable proportions of apatite–phlogopite–magnetite ± pyrochlore ± metasomatic Na–Ca amphiboles ± zircon. Early high-Sr calcite carbonatites (4,800–6,060 ppm Sr; La/YbCN = 31.6–41.5; δ13C = −4.2 to −4.0 ‰) possibly were derived from a carbonated silicate parental magma by fractional crystallization. Associated high-Sr dolomite carbonatites (4,090–6,310 ppm Sr; La/YbCN = 96.5–352) and a late-stage, narrow, high rare earth element (REE) dolomite carbonatite dyke (La/YbCN = 2756) define a shift in the C–O stable isotope data (δ18O = 7.5 to 12.6 ‰; δ13C = −4.2 to −2.2 ‰) from the primary carbonatite field that may have been produced by Rayleigh fractionation with magma crystallization and cooling or through crustal contamination via fluid infiltration. Past exploration has focussed primarily on the secondary monazite-(Ce)-rich REE and U mineralization in the oxidized zone overlying the carbonatite. However, high-grade primary hydrothermal REE mineralization also occurs in narrow (<1 m wide) shear-zone hosted lenses of apatite–monazite-(Ce) and foliated monazite-(Ce)–talc rocks (≤∼25.8 wt% total rare earth oxide (TREO); La/YbCN = 30,085), as well as in high-REE dolomite carbonatite dykes (3.43 wt% TREO), where calcite, parisite-(Ce) and synchysite-(Ce) replace monazite-(Ce) after apatite. Primary magmatic carbonatites were widely hydrothermally dolomitized to produce low-Sr dolomite carbonatite (38.5–282 ppm Sr; La/YbCN = 38.4–158.4; δ18O = 20.8 to 21.9 ‰; δ13C = −4.3 to −3.6 ‰) that contains weak REE mineralization in replacement textures, veins and coating vugs. The relatively high δD values (−54 to −34 ‰) of H2O derived from carbonatites from the CRCC indicate that the fluids associated with carbonate formation contained a significant amount of crustal component in accordance with the elevated δ13C values (∼−4 ‰). The high δD and δ13C signature of the carbonatites may have been produced by CO2–H2O metasomatism of the mantle source during Paleoproterozoic subduction beneath the eastern margin of the Kimberley Craton.